Pengaruh Motivasi dan Pengalaman Kerja Terhadap Kinerja Karyawan PT Top Ambulance - Adilla fitriansyah; Hasanah Hasanah (As-Syirkah: Islamic Economic & Financial Journal, 2026)
This study aims to analyze the effect of motivation and work experience on employee performance at PT Top Ambulance. This research is motivated by the crucial role of human resources in health service companies that require speed, accuracy, and service quality. A quantitative approach with an associative research design was employed. The population consisted of all 45 employees of PT Top Ambulance, using a saturated sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression. The results indicate that motivation has a positive and significant effect on employee performance, work experience also has a positive and significant effect, and both variables simultaneously influence employee performance. The findings provide practical implications for management in improving employee performance through motivation enhancement and experience management.